DSACNN: Dynamically local self-attention CNN for 3D point cloud analysis. (October 2022) - Song, Yupeng; He, Fazhi; Fan, Linkun; Dai, Jicheng; Guo, Qing
Abstract: The point cloud is a common 3D representation widely applied in CAX engineering due to its simple data representation and rich semantic information. However, discrete and unordered 3D data structures make it difficult for point clouds to understand semantic information and make them unsuitable for applying standard operators. In this paper, to enhance machine perception of 3D semantic information, we propose a novel approach that can not only directly process point cloud data by a novel convolution-like operator but also dynamically pay attention to local semantic information. First, we design a novel dynamic local self-attention mechanism that can dynamically and flexibly focus on top-level information of the receptive field to learn and understand subtle features. Second, we propose a dynamic self-attention learning block, which adopts the proposed dynamic local self-attention learning convolution operation to directly deal with disordered and irregular point clouds to learn global and local point features while dynamically learning the important local semantic information. Third, the proposed operation can be compatibly applied as an independent component in popular architectures to improve the perception of local semantic information. Numerous experiments demonstrate the advantage of our method for point cloud tasks on datasets from both CAD data and scan data of complex real-world scenes.